2019
DOI: 10.1002/cam4.2422
|View full text |Cite
|
Sign up to set email alerts
|

High aldehyde dehydrogenase activity at diagnosis predicts relapse in patients with t(8;21) acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) with t(8;21) is a heterogeneous disease. Although the detection of minimal residual disease (MRD), which is indicated by RUNX1‐RUNX1T1 transcript levels, plays a key role in directing treatment, risk stratification needs to be improved, and other markers need to be assessed. A total of 66 t(8;21) AML patients were tested for aldehyde dehydrogenase (ALDH) activity by flow cytometry at diagnosis, and 52 patients were followed up for a median of 20 (1‐34) months. The median percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Several studies have identified a specific subset of LSCs with high ALDH expression that are quiescent and resistant to chemotherapy [ 58 – 60 ]. In addition, patients with a high percentage of ALDH + LSCs are associated with a poor prognosis and adverse clinical outcomes [ 61 , 62 ]. An assessment of the ALDH level in KG1a cells in classical 2D cultures did not show any significant difference with respective controls (Figure S7 ), but KG1a cells in the 3D mono-culture model did, with a Chi-square value of around 15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified a specific subset of LSCs with high ALDH expression that are quiescent and resistant to chemotherapy [ 58 – 60 ]. In addition, patients with a high percentage of ALDH + LSCs are associated with a poor prognosis and adverse clinical outcomes [ 61 , 62 ]. An assessment of the ALDH level in KG1a cells in classical 2D cultures did not show any significant difference with respective controls (Figure S7 ), but KG1a cells in the 3D mono-culture model did, with a Chi-square value of around 15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In AML, high aldehyde dehydrogenase activity at diagnosis predicts relapse in patients with t(8;21) AML [40]. In general, evidence has been mounting that the protein family of the aldehyde dehydrogenases plays a role in the development of AML; yet the interpretation of their exact biological effect on AML progression remains debatable [41].…”
Section: Aldh Activity In Acute Leukemiamentioning
confidence: 99%
“…ALDH-positive (ALDH + ) leukemia cells have greater tumorigenicity and chemotherapy resistance compared to ALDH-negative cells [ 14 , 15 ]. Additionally, high ALDH activity at diagnosis predicts relapse in a subset of AML patients [ 16 ]. Among the 19 ALDH isoforms identified in humans, the most prominent are ALDH1 isoforms (ALDH1A1-3, ALDHB1, and ALDH1L1&2) and the ALDH2 isoform.…”
Section: Introductionmentioning
confidence: 99%